The law applicable to employment contracts under the Rome I-Regulation - Czerwiński, Marcin (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
Private international law is of great practical importance in the European Union, especially for the proper functioning of the internal market. It has been enacted mainly in the form of the Rome I-Regulation. The question of which national law applies in a cross-border case is often decisive with regard to employment contracts, because national substantive employment laws remain extremely diversified. The first aim of this paper is to outline the major issues relating to conflict-of-laws rules concerning the employment relationship. The second aim is to show the scope of the freedom to choose the law applicable to the employment relationship. The employment relationship, like any contractual relationship, can be subject to the law chosen by the parties but this choice has limited practical importance. The priority is therefore the protection guaranteed to the employee under the law of the state indicated by objective hyphens.